A Faktor-faktor Keputusan Nasabah Dalam Memilih Produk Tabungan Syariah (Studi Kasus Bank BTN Syariah Kantor Cabang Solo) - Haniin, Umi; Irsan Angga Setiawan; Wikan Budi Utami (Jurnal Ilmiah Ekonomi Islam, 2026)
Purpose of this study is to find out how the factors of customer decisions in choosing Islamic Bank Savings products. This study aims to examine cultural, social, personal and psychological factors that influence customers in selecting Islamic bank savings products. The population in this study were customers of Bank BTN Syariah Solo Branch Office. Determination of the sample in this study using a sampling technique with Incidental Sampling technique. Incidental Sampling is taking respondents as a sample based on coincidence, namely customers who have saved money and anyone who meets the researcher by chance at the BTN Syariah Solo Branch Office can be used as a sample. Analysis using linear regression with a significant level (a) 0.05. The results of this study indicate that: (1) Cultural factors do not significantly influence customer decisions in choosing Bank BTN Syariah Solo Branch Office. This is because customers choose Bank BTN Syariah Solo Branch Office not because of the culture or habits that exist around them, for example the majority of the population of Solo City or the majority of Indonesia's population are Muslims. (2) Social factors have no significant effect on customer decisions in choosing Bank BTN Syariah Solo Branch Office. This is because customers choosing Bank BTN Syariah Solo Branch Office do not pay attention to reference groups such as recommendations from neighbors and friends or required by family. (3) Personal factors have a significant effect on customer decisions in choosing Bank BTN Syariah Solo Branch Office. This is caused by the perception and implementation of usury in accordance with customer beliefs. (4) Psychology factors have a significant effect on customer decisions in choosing Bank BTN Syariah Solo Branch Office. This is due to the existence of motivation within him that can meet his needs.